Application Value of Transcranial Direct Current Stimulation in Stroke Patients - Haq, Usman; Aftab, Alishba; Malik, Mohammad Hamza Bin Abdul; Haq, Ali; Malik, Muhammad Awais Bin Abdul; Rashid, Amna (Archives of Clinical and Biomedical Research, 2022)
Objectives: The main objective of the study is to analyze the application value of transcranial direct current Stimulation (TDCS) in stroke patients. Material and Methods: This pilot study was conducted in Rawal Institute of Health Sciences during June 2019 to June 2020. The components required for TDCS include a Constant Current Stimulator and surface electrodes soaked in normal saline. A Constant Current Stimulator provides a steady flow of direct current (e.g., 0–4mA) while constantly monitoring the resistance in the system. Results: The study was completed by 136 patients. Their mean age was 53.2 ± 8.4 years (range: 36–61 years). There were more males than females (60% vs. 40%). Their demographic and clinical characteristics are summarized in table 1. Conclusion: It is concluded that TDCS combined with VR can reduce motor impairment, improve function, increase ADL in the affected upper limb in patients with subacute or chronic ischemic stroke than VR alone.